Essays on Entrepreneurship - Engel, Anna Erica; Justus Liebig University Giessen (My University, 2024)
This dissertation examines the psychological and behavioral dimensions of entrepreneurship, emphasizing the critical role of entrepreneurial passion (EP), personality traits, and personal values in shaping entrepreneurial processes and outcomes. By integrating psychological theories within a strategic management framework, this research contributes to both academic discourse and practical applications in entrepreneurship. The first study conducts a systematic literature review of 74 papers on EP, exploring its influence on entrepreneurial behavior, motivation, and performance. It highlights EP as a key driver of creativity, resilience, and risk-taking, and provides insights into how passion enhances entrepreneurial success and commitment. The second study uses a novel Twitter analysis to examine the personal values of venture capitalists (VCs) and business angels (BAs), revealing distinct differences in their priorities. VCs value security, achievement, and self-improvement, while BAs value mentorship and inspiration. These findings provide actionable insights for entrepreneurs to align their strategies with investor preferences. The third study analyzes changes in personality traits of Indian and American tech entrepreneurs before and after COVID-19, using the Big Five personality model and Hofstede's cultural dimensions. Results indicate significant shifts in openness and extraversion due to the pandemic, shaped by cultural and contextual factors. These findings underscore the dynamic nature of entrepreneurial traits in response to global crises.
Keywords: Entrepreneurship; Entrepreneurial Passion; Entrepreneurial Behaviour; ddc:330